EFFECT OF EXTRACTION METHOD VARIATIONS ON THE QUALITY OF VIRGIN COCONUT OIL (VCO) - Pratama, Gusti Randy; Andiyono; Junardi; Hajijah; Narni (Agripreneur : Jurnal Pertanian Agribisnis, 2024)
Virgin Coconut Oil (VCO) is an unrefined oil obtained by the extraction of coconut flesh. The extraction procedure influences the sustainability of VCO commercialization. The challenges posed by the agro-industry in extracting coconut oil using various extraction processes deserve additional investigation. This study aimed to identify the effect of different extraction methods on VCO quality and to select the optimal VCO extraction method. The study utilized a single factor Completely Randomized Design (CRD) with three replications. Natural fermentation, induction fermentation, enzymatic, freezing, and heating were among the extraction methods employed. The observed responses were moisture content, free fatty acid content, and peroxide value. The findings revealed that different extraction procedures did not affect VCO's moisture content. The free fatty acid content changed dramatically. The freezing approach was the most effective treatment for free fatty acid response, with a value of 0.058%. Variations in extraction procedures significantly influenced the peroxide value response. The enzymatic approach produced the best peroxide value response (0.12 mg ek/kg).